Improving qur’anic fashahah through the wahdah method: A quasi-experimental study in a madrasah aliyah - Firdaus, Muhammad Raffi; Baharudin, Baharudin (STAI Auliaurrasyidin Tembilahan, 2026)
While the Wahdah method is widely recognized for increasing the quantity of Qur’anic memorization, its specific effectiveness in improving recitation quality particularly faṣḥahah, encompassing fluency, articulatory accuracy, and proper application of tajwīd rules within formal madrasah settings remains underexplored. Qur’an Hadith instruction at the Madrasah Aliyah level commonly relies on conventional memorization-based practices that insufficiently address these qualitative aspects of recitation. This study aimed to examine the effectiveness of the Wahdah method in enhancing students’ faṣḥahah ability in a formal Madrasah Aliyah context. Using a quasi-experimental posttest-only control group design, the research was conducted at MAN 1 Bandar Lampung and involved two Grade XI classes selected through cluster sampling, assigned as experimental and control groups. Students’ faṣḥahah ability was assessed using a validated performance-based recitation instrument measuring fluency, articulatory precision (makhārij al-ḥurūf accuracy), and correct application of tajwīd rules. Data were analyzed using an Independent Samples t-test after confirming variance homogeneity. The results indicated a statistically significant difference between groups, with the experimental group achieving higher mean faṣḥahah scores than the control group (t (57) = 2.076, p = 0.042). Classroom observations supported these findings, revealing fewer articulation errors and more consistent tajwīd application among students exposed to intensive verse by verse repetition. The study concludes that the Wahdah method is a pedagogically effective approach, offering madrasah teachers a structured and practice-oriented technique to systematically improve students’ faṣḥahah by integrating memorization with sustained recitational accuracy.